Site-directed RNA editing (SDRE): Off-target effects and their countermeasures. (20th November 2019) - Mao, Shaoshuai; Liu, Yajing; Huang, Shisheng; Huang, Xingxu; Chi, Tian
Abstract: Site-directed RNA editing (SDRE) is invaluable to basic research and clinical applications and has emerged as a new frontier in genome editing. The past few years have witnessed a surge of interest in SDRE, with SDRE tools emerging at a breathtaking pace. However, off-target effects of SDRE remain a tough problem, which constitutes a major hurdle to their clinical applications. Here we discuss the diverse strategies for combating off-target editing, drawing lessons from the published studies as well as our ongoing research. Overall, SDRE is still at its infancy, with significant challenges and exciting opportunities ahead.